Rancang Bangun Aplikasi Perpustakaan Berbasis Android Menggunakan Mit App Inventor - Indra Kusuma Wardani; Zanuar Rifa’i (STMIK Sumedang, 2021)
An Android-based library information system is something that is no wonder anymore in the world of education or the workforce.Android itself is a very popular platform in the current century.In the advancement of a technology, therefore the library as a window of the world requires Android to improve a performance of its operation to get the results achieved.Similarly, the village of Klaces in the operation of the library is still a lot of problems arising to require a settlement process, because the library is obliged to present accurate information precisely and can provide its own satisfaction for workers and visitors.Klaces Village is one of the government in Kampung Laut Sub-district and is located in Cilacap Regency.Currently the government of Klaces village already has a library that has been utilized by various school communities and other institutions that are located adjacent to Klaces Village office which is still in the form of manual, so it needs an Android-based library information system that can later help in the operation of the software.The result of this research is to produce a library application with several other features, book stock, List of visitors, book borrowing, book returns and stock procurement of books.In designing the library system using app inventor application and using System method Extreme Programming